Prospects for Abiotic Stress Tolerance in Crops Utilizing Phyto- and Bio-Stimulants - Rai, Nidhi; Rai, Shashi Pandey; Sarma, Birinchi Kumar (Frontiers in Sustainable Food Systems, 2021)
Environmental stressors such as salinity, drought, high temperature, high rainfall, etc. have already demonstrated the negative impacts on plant growth and development and thereby limiting productivity of the crops. Therefore, in the time to come, more sustainable efforts are required in agricultural practices to ensure food production and security under such adverse environmental conditions. A most promising and eco-friendly way to achieve this goal would be to apply biostimulants to address the environmental concerns. Non-microbial biostimulants such as humic substances (HA), protein hydrolysate, plant-based products and seaweed extracts (SWE), etc. and/or microbial inoculants comprising of plant growth-promoting microbes such as arbuscular mycorrhizal fungi (AMF), fluorescent and non-fluorescent Pseudomonas, Trichoderma spp., Bacillus spp. etc. have tremendous potentiality to enhance plant growth, flowering, crop productivity, nutrient use efficiency (NUE) and translocation, as well as enhancing tolerance to a wide range of abiotic stresses by modifying physiological, biological and biochemical processes of the crop-plants. Similarly, application techniques and timing are also important to achieve the desired results. In this article we discussed the prospects of using seaweed, microbial, and plant-based biostimulants either individually or in combination for managing environmental stresses to achieve food security in a sustainable way. Particular attention was given to the modifications that take place in plant's physiology under adverse environmental conditions and how different biostimulants re-program the host's physiology to withstand such stresses. Additionally, we also discussed how application of biostimulants can overcome the issue of nutrient deficiency in agricultural lands and improve their use efficiency by crop plants.